If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + 3x + -7 = 9 Reorder the terms: 11 + -7 + 3x = 9 Combine like terms: 11 + -7 = 4 4 + 3x = 9 Solving 4 + 3x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = 9 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 9 + -4 3x = 9 + -4 Combine like terms: 9 + -4 = 5 3x = 5 Divide each side by '3'. x = 1.666666667 Simplifying x = 1.666666667
| 106=-7(p-7)+1 | | -1=-10/9x+10 | | -1=-10/9+10 | | -16-5x=5-sx | | (4x-3)/5=(2x-7)/8 | | -1.1111=-10/9x+10 | | -1.1111=-10/9+10 | | 82=4x-2(1-4x) | | -10/9*-1.1111+10 | | 4/3*6.4615-8=y | | -1/2*-5 | | -x/2+5=-1 | | x/4-2=-7 | | 4(3g-5)=52 | | 2x-1=z+2 | | (4/3x)-8=(-8/7x)+8 | | 4/3-8=-8/-7+8 | | 4/3x-8=-8/7+8 | | 0=4/3x-8 | | -4+3x+2x=36 | | 0=-8/7x+8 | | 3/4m | | 3.8x=2.6x | | 0=-8/7+8 | | m+11=5m+9 | | 1/2p-7=9(-27) | | 1/2p-7(-27) | | -34-4x=13-10x | | x^4+20x^2+64=0 | | 4/3(-8)-8 | | (4/3)(-8)-8 | | 526.25-200= |